Pengembangan Karakter Toleran Siswa Melalui Pendekatan Saintifik Dalam Pembelajaran Ipa di SDN Pajagalan 2 Kabupaten Sumenep - Dewi, Ike Yuli Mestika; Stefany, Debrine (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
Education is considered to be a strategic tool in shaping the character of the nation, so that it can solve the social problems of national life which begin to lose the character of a civilized nation. Reorienting the educational process as a center of community education, in truth must be revitalized again in its entirety, so that the world of education can be the center and the right place in empowering students, motivated and freed from their helplessness. Characterized education is absolutely necessary from an early age, especially in basic education through science learning with a scientific approach. With a scientific approach, science learning is expected to be one way to strengthen the character of students, so that they can make a real contribution in nation building towards a nation of character. The research developed by this author is a type of development research that emphasizes the development of integrated learning tools for elementary schools of the nested type in natural science learning to develop student tolerant character. The application of learning tools is carried out using The One Group Pretest-Postest Design research design. While the data collection techniques used in this study consisted of 3 techniques, namely observation, tests and questionnaires. With a number of tools developed during the study process, it has been able to effectively develop student tolerance. Various tolerant indicators as explained above, have been able to become part of students' attitudes, so they can be used as a barometer in the development of other materials. The results of the recapitulation of students' knowledge, skills and attitudes which were emphasized on a number of aspects, both aspects of peace, respect for differences and awareness, generally reached figures ranging from 76 to 100. It was confirmed that the science learning process undertaken, was able to have a positive impact in developing tolerant character among students.